Analisis Manajemen Kurikulum dan Pembelajaran Sekolah Alam dalam Mengembangkan Nilai Karakter Religius pada Kelas IV di SDIT Alam Nurul Islam Dua Ngawi - kamila Al Farisi; Prima Rias wana; Widya Pangestu (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2023)
The purpose of this study is to find out that learning activities with the help of Quizlet can affect the ability of fifth grade students at SDN Sayabulu, especially in critical thinking skills. Before conducting the research, the researcher interviewed the homeroom teacher and one of the fifth grade students of SDN Sayabulu that the learning process rarely uses technology, teachers more often teach using conventional methods with the help of book media. Students' interest in learning can be reduced because one of the media is less varied so that it affects the development of students' critical thinking. From the results of these observations and interviews, researchers used an alternative learning media, namely Quizlet in learning activities in order to require students to think critically. Quizlet itself consists of several interesting features that can help students in learning, features such as flashcards, tests, and writing which emphasizes that students understand, analyze, identify, and provide answers to challenging questions or questions that require analysis and evaluation.learning Quizlet is expected to be a way out in improving the critical thinking skills of SDN Sayabulu students. The research was conducted at SDN Sayabulu which is located on Jl. Sayabulu, Serang City, Banten Province, with the research time in May 2022. The study population consisted of 42 fifth grade students at SDN Sayabulu, of which 38 students were sampled using probability sampling calculations. The researcher uses a quantitative method, namely the form of a one group pre-test post-test which includes the type of pre-experimental design to compare critical thinking of the fifth grade students of SDN Sayabulu before and after treatment with the Quizlet contained in one group or class. The results of the study using Quizlet for learning media, showed a significant increase, it was in the calculation of the parametric test by using the paired sample t test with the results of the sig.2 tailed value of 0.000 < 0.05, meaning that Ha learning media was accepted, then the influence of Quizlet in improve critical thinking of fifth grade students at SDN Sayabulu. Character education is a very important education to be applied to students. But education at this time has been disorientated in education, where religious education is separated from other education, so that is has an impact on the difficulty of developing the values of religious character. And the nedd special research in developing the value of religius character in students. This study analyzes the management and learning of the natural school curriculum in developing the values of religious character in grade IV A of the SDIT Alam Nurul Islam Dua. The purpose of this study is to find out the management of the natural school curriculum and the implementation of learning in developing religious character values in the classroom and outside the classroom. And to find out the inhibiting factors in the implementation of the process and also to find out how to overcome the inhibiting factors. The object under study was grade IV A at the SDIT Alam Nurul Islam Dua with data taken from interviews with teachers and school principals and also observations made to grade IV A students. The research used a qualitative descriptive approach. The data sources for this study were the principal, vice principal of the curriculum section, the mentor teacher and the assistant teacher (homeroom teacher) IV A SDIT Alam Nurul Islam Dua. Data collection techniques were obtained through observation, in depht interviews and sicumentation. Then the data obtained was analysis with the Miles and Huberman model with data reduction steps, data presentation, conclusions about the research. The results obtained are that the management of the salam school curriculum is carried our starting from planning, organizing, implementing, and evaluating like school in general. In educational learning intergated with religiuos character values, as well as supporting activities in developing religiuos character values in the hope of providing habituation that is able to attach to the character or nature of students. While the facors that hinder the omplementation are consistency in carrying out aactivities for students while at home so that is affects student at school.